OPTIMIZATION OF CUTTING PARAMETERS USING THE RESPONSE SURFACE METHOD - Guvercin, Salih; Yıldız, Aytaç (Yildiz Technical Univ, 2018)
Some cutting parameters have to be considered in order to obtain high-quality surfaces in machining. Because poorly selected cutting parameters cause both the cutting tools to wear out quickly and the surface to become rough. Therefore, it is of great importance to use experimental design methods to obtain better quality surfaces with an optimal combination of cutting parameters. In this study, optimization of cutting parameters such as feed rate, cutting speed and depth of cut, which affects the surface roughness of AISI 1040 steel the commonly used in the industry, is aimed by three-level Box-Behnken design combined with response surface methodology. For this purpose, 15 workpieces with empty set 70 mm and 200 mm length were prepared and machined on a CNC lathe. Then, the surface roughness values of the workpieces were measured. The obtained surface roughness values were analyzed in the Design Expert 10.0.6 program and the cutting parameters affecting the surface roughness were optimized. According to the results obtained from the study, it was determined that the feed rate is the parameter that has the greatest effect on the surface roughness. In addition, optimum surface roughness was determined by a feed rate of 0.2 mm/rev, a cutting speed of 397.58 m/min and a depth of cut 1.5617 mm.
Keywords: Box-Behnken design; response surface methodology; surface roughness